TEORI-TEORI GOOD CORPORATE GOVERNANCE (GCG) DALAM PERSPEKTIF PERBANKAN SYARIAH DI INDONESIA - Ali Safran Pasaribu; Farisa Nadhila Siregar; Fikry Haikal (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This article discusses major theories underlying Good Corporate Governance (GCG) and analyzes their relevance in the context of Islamic banking in Indonesia. Using a qualitative descriptive approach through an extensive literature review, this study elaborates agency theory, stewardship theory, stakeholder theory, transaction cost theory, political theory, and resource dependence theory. The findings indicate that each theory provides complementary insights in explaining governance mechanisms, conflicts of interest, accountability, and sustainability of Islamic financial institutions. The integration of these theories is crucial to strengthen governance practices, prevent internal fraud, and maintain public trust. This study contributes conceptually by expanding governance discourse within Islamic banking and practically by offering guidance for improving GCG implementation.